De Novo Aneurysm Formation in Carriers of Saccular Intracranial Aneurysm Disease in Eastern Finland. Issue 5 (May 2016) - Lindgren, Antti E.; Räisänen, Sari; Björkman, Joel; Tattari, Hanna; Huttunen, Jukka; Huttunen, Terhi; Kurki, Mitja I.; Frösen, Juhana; Koivisto, Timo; Jääskeläinen, Juha E.; von und zu Fraunberg, Mikael
Abstract : Background and Purpose—: Formation of new (de novo) aneurysms in patients carrying saccular intracranial aneurysm (sIA) disease has been published, but data from population-based cohorts are scarce. Methods—: Kuopio sIA database (http://www.uef.fi/ns ) contains all unruptured and ruptured sIA patients admitted to Kuopio University Hospital from its Eastern Finnish catchment population. We studied the incidence and risk factors for de novo sIA formation in 1419 sIA patients with ≥5 years of angiographic follow-up, a total follow-up of 18 526 patient-years. Results—: There were 42 patients with a total of 56 de novo sIAs, diagnosed in a median of 11.7 years after the first sIA diagnosis. The cumulative incidence of de novo sIAs was 0.23% per patient-year and that of subarachnoid hemorrhage from a ruptured de novo sIA 0.05% per patient-year. The risk of de novo sIA discovery per patient-year increased with younger age at the first sIA diagnosis: 2.2% in the patients aged <20 years and 0.46% in the patients aged between 20 and 39 years. In Cox regression analysis, smoking history and younger age at the first sIA diagnosis significantly associated with de novo sIA formation, but female sex, multiple sIAs, and sIA family did not. Conclusions—: Patients aged < 40 years at the first sIA diagnosis are in a significant risk of developing de novo sIAs, and they should be scheduled for long-term angiographic follow-up. Smoking increases the risk of de novo sIA formation, suggesting long-term follow-up for smokers. Antismoking efforts are highly recommended for sIA patients.